PENERAPAN PUNISHMENT POINT SYSTEM DALAM TATA TERTIB SEKOLAH UNTUK MENINGKATKAN KEDISIPLINAN SISWA (Studi Kasus di SMP Negeri 1 Ciamis) - Dicka Sutrisna Putra, - (2021)
The low level of student discipline in schools is still one of the educational problems that need to be resolved immediately, because if not, it will certainly disrupt the success of education itself. Punishment point system is a system of punishment to increase student compliance to school rules without any physical sanctions, each violation is given a point according to the level of violation and accumulated to certain points with certain consequences from summoning their parents to being expelled from school. The general objective of this study was to determine the effect of the implementation of the punishment point system in school rules to improve the student discipline, especially in SMP Negeri 1 Ciamis. The research was conducted with a qualitative approach using the case study method. The data collection techniques used were observation, interview and documentation study. The results of the study conclude that: (1) the implementation of the punishment point system in the school rules is carried out based on applicable laws and regulations involving all related parties (stake holders), (2) the obstacles faced in implementing the punishment point system in school discipline include socialization problems and administratively, (3) efforts made to overcome the obstacles faced are to use every opportunity (routine teacher and education staff meetings and flag ceremonies) for socialization, and (4) the application of the punishment point system in the school rules has positive implications for student discipline. Keywords: school rules, punishment point system, student discipline